Common TGFβ2, BMP4, and FOXC1 variants are not associated with primary open-angle glaucoma - Park, Soo (Molecular Vision, 2012)
PURPOSE: Primary open-angle glaucoma (POAG) is a common but complex disease with a strong genetic component. Notably, few genes have been robustly associated with POAG. An obvious group of genes to test as susceptibility factors for POAG are the developmental genes forkhead box C1 (FOXC1), transforming growth factor-beta 2 (TGFβ2), and bone morphogenic protein 4 (BMP4). These genes are known to play important roles in the normal morphogenesis of the anterior segment and/or have been implicated in intra-ocular pressure (IOP) regulation and trabecular meshwork function. This study investigates the role of FOXC1, TGFβ2, and BMP4 in POAG. METHODS: The contribution of common genetic variation at the FOXC1, TGFβ2, and BMP4 loci to risk of POAG was investigated in a case-control association study in 330 British Caucasian individuals comprised of 272 high-tension glaucoma (HTG) and 58 ocular hypertension (OHT), and 276 matched controls. RESULTS: All the single nucleotide polymorphisms (SNPs) were in Hardy–Weinberg equilibrium and genotyping success rate was >92% for all SNPs. With the exception of a weak association between the BMP4 tagging SNP rs2761884 and the combined patient group HTG+OHT that did not withstand permutation testing (uncorrected p=0.0400, corrected p=0.1320), no associations (p<0.05) were identified between the patient groups (HTG and OHT) and FOXC1, TGFβ2, and BMP4 alleles and haplotypes compared to the control group. CONCLUSIONS: This is the first association analysis of FOXC1, TGFβ2, and BMP4 and POAG. These genes were selected as candidate genes for POAG because of their biologic roles. No significant associations were identified between FOXC1, TGFβ2, and BMP4 alleles and haplotypes and POAG. The lack of association suggests that common variation in these genes do not have a significant role in the pathogenesis of POAG among British Caucasian subjects.